Surface‐Induced Selection During In Situ Photoswitching at the Solid/Liquid Interface1. (27th February 2015) - Bonacchi, Sara; El Garah, Mohamed; Ciesielski, Artur; Herder, Martin; Conti, Simone; Cecchini, Marco; Hecht, Stefan; Samorì, Paolo
Abstract Here we report for the first time a submolecularly resolved scanning tunneling microscopy (STM) study at the solid/liquid interface of the in situ reversible interconversion between two isomers of a diarylethene photoswitch, that is, open and closed form, self‐assembled on a graphite surface. Prolonged irradiation with UV light led to the in situ irreversible formation of another isomer as by‐product of the reaction, which due to its preferential physisorption accumulates at the surface. By making use of a simple yet powerful thermodynamic model we provide a quantitative description for the observed surface‐induced selection of one isomeric form.